Liquid-based cytology versus conventional cytology in fine-needle aspirates of salivary gland neoplasms - Madhu Kumar; Shweta Katiyar; Mala Sagar; Malti Kumari; Madhu Mati Goel (Wolters Kluwer Medknow Publications, 2018)
Background: Liquid-based cytology (LBC) is a method of retrieving and processing of cytological material for the assessment of both gynecological and nongynecological cases introduced in 1996. Mostly conventional smears (CS) are prepared in Indian scenario; however, due to increasing popularity of LBC in nongynecology specimens, LBC is also used in few centers for diagnosing salivary gland neoplasm. Aim: The aim of this study is to compare CS and LBC in fine-needle aspiration cytology (FNAC) of the salivary gland neoplasms in terms of cytomorphological details, adequacy, ease of interpretation, pitfalls, and diagnostic efficiency. Materials and Methods: We conducted a prospective, observational, comparative study which included 64 salivary gland neoplasms. Both CS and LBC (SurePath) were prepared as per standard protocols and examined. Results and Conclusion: In our study, specificity and positive predictive value of both the techniques (conventional and LBC) were found to be 100%. Sensitivity of both the techniques was found to be similar (66.7%). Negative predictive value and diagnostic accuracy of conventional technique were found to be almost similar to that of LBC technique (97.6% vs. 97.2% and 97.7% vs. 97.4%). In terms of adequacy and cellularity, CSs were better than LBC. Ease of interpretation was better with CSs due to abundant chondromyxoid stroma, an important clue in the diagnosis of pleomorphic adenoma. Nuclear details and background were better in LBC as compared to CS. Hence, we conclude that in salivary gland FNAC, both CS and LBC have similar diagnostic efficiency. however, interpretation of conventional smears is easier than Liquid Based Cytology especially in cases of pleomorphic adenoma. However, some advantages of LBC in respect to conventional cytology, with better-preserved morphology obtained from LBC becomes furthermore obligatory.